Local tissue interactions govern pLL patterning in medaka - Seleit, Ali; Groß, Karen; Onistschenko, Jasmin; Hoang, Oi Pui; Theelke, Jonas; Centanin, Lázaro (Developmental biology, 2021)
Vertebrate organs are arranged in a stereotypic, species-specific position along the animal body plan. Substantial morphological variation exists between related species, especially so in the vastly diversified teleost clade. It is still unclear how tissues, organs and systems can accommodate such diverse scaffolds. Here, we use the distinctive arrangement of neuromasts in the posterior lateral line (pLL) system of medaka fish to address the tissueinteractions defining a pattern. We show that patterning in this peripheral nervous system is established by autonomous organ precursors independent of neuronal wiring. In addition, we target the keratin 15 gene to generate stuck-in-the-midline (siml) mutants, which display epithelial lesions and a disrupted pLL patterning. By using siml/wt chimeras, we determine that the aberrant siml pLL pattern depends on the mutant epithelium, since a wild type epithelium can rescue the siml phenotype. Inducing epithelial lesions by 2-photon laser ablation during pLL morphogenesis phenocopies siml genetic mutants and reveals that epithelial integrity defines the final position of the embryonic pLL neuromasts. Our results using the medaka pLL disentangle intrinsic from extrinsic properties during the establishment of a sensory system. We speculate that intrinsic programs guarantee proper organ morphogenesis, while instructive interactions from surrounding tissues facilitates the accommodation of sensory organs to the diverse body plans found among teleosts.